(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
In this article we present the results of a diachronic study of the Spanish locution “a mano” “at hand” from the 13th to the 15th century. The analysis accounts for their evolution from a prepositional phrase that undergoes syntactic and semantic changes to become an adverbial locution in the fifteenth century, a process that in terms of our approach is a case of grammaticalization.